Vancouver: Art and Artists 1931-1983. - Farrell-Ward, Lorna; Shadbolt, Jack; Rogatnick, Abraham; Pakasaar, Helga (Vancouver : Vancouver Art Gallery, 1983)
Alexander, Paul ; Amess, Fred ; Anderson, John ; André, Françoise ; Arden, Roy ; Aspell, Peter ; Banana, Anna ; Bates, Maxwell ; Baxter, Iain ; Bell, Alistair ; Bentley, Percy ; Binning, Bertram C. ; Black, Byron ; Bluesinger, Taki ; Bobak, Bruno ; Bradley, Randy ; Braidwood, Tom ; etc.
Vancouver: Art and Artists 1931-1983, An inaugural exhibition in celebration of the opening of the new Vancouver Art Gallery at Robson Square, October 15th to December 31st, 1983
English
kunstcatalogus
Keywords: Vancouver